Antioxidant activity of isocoumarins isolated from Paepalanthus bromelioides on mitochondria - Devienne, Karina F.; Calgaro-Helena, Anaisa F.; Dorta, Daniel J.; Prado, Ieda M. R.; Raddi, Maria Stella G.; Vilegas, Wagner [UNESP]; Uyemura, Sergio A.; Santos, Antonio C.; Curti, Carlos (Elsevier B.V., 2007)
The isocoumarins (1-50 mu M) paepalantine (9,10-dihydroxy-5,7-dimethoxy-1H-naptho(2,3c)pyran-1-one), 8,8 '-paepalantine dimer, and vioxanthin isolated from Paepalanthus bromelioides, were assessed for antioxidant activity using isolated rat liver mitochondria and non-mitochondrial systems, and compared with the flavonoid quercetin. The paepalantine and paepalantine dimers, but not vioxanthin, were effective at scavenging both 1,1-diphenyl-2-picrylhydrazyl (DPPH*) and superoxide (O-2(-)) radicals in non-mitochondrial systems, and protected mitochondria from tert-butylhydroperoxide-induced H2O2 accumulation and Fe2+ -citrate-mediated mitochondrial membrane lipid peroxidation, with almost the same potency as quercetin. These results point towards paepalantine, followed by paepalantine dimer, as being a powerful agent affording protection, apparently via O-2(-) scavenging, from oxidative stress conditions imposed on mitochondria, the main intracellular source and target of those reactive oxygen species. This strong antioxidant action of paepalantine was reproduced in HepG2 cells exposed to oxidative stress condition induced by H2O2. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Paepalanthus bromelioides; eriocaulaceae; isocournarins; paepalantine; mitochondria; reactive oxygen species; oxidative stress; membrane lipid peroxidation